CÔNG THỨC BẠCH CẦU CỦA MÁU NGOẠI VI CÙNG CÁC CƠ QUAN TẠO MÁU Ở LOÀI CÁ LÓC ĐỒNG Channa striata (Bloch, 1793) VÀ LƯƠN Monopterus albus (Zuiew, 1793) THU TỪ VƯỜN QUỐC GIA CÁT TIÊN (VIỆT NAM) - Gordeev , Y.Y.; Mikryakov, D.V.; Suvorova , T.A. (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE LEUKOCYTE FORMULA OF PERIPHERAL BLOOD AND HEMATOPOIETIC ORGANS OF Channa striata (Bloch, 1793) AND Monopterus albus (Zuiew, 1793) FROM CATTIEN NATIONAL PARK (VIETNAM)The composition of leukocytes of peripheral blood of the snakehead Channa striata and rice eel Monopterus albus and the hematopoietic organs of the snakehead was investigated. It was established that the leukocytes of C. striata and M. albus were heterogeneous in terms of morphofunctional characteristics and different by cell structures: lymphocytes, monocytes, neutro-, eosinophils and blast cells. The compositions of blood leukocytes and hematopoietic organs were dominated by lymphocytes, following by blast forms of cells and a small percentage of granulocytes and monocytes/macrophages. Two types of granulocytes were revealed in the striped snakehead: neutrophils and eosinophils, while in rice eel - only neutrophils.